Development and Characterization of Novel Vesicular System using Purpurin-Phosphatidyl Choline as a Skin Antiaging Agent - Soni, Vandana (Asian Journal of Pharmaceutics (AJP), 2019)
Introduction: Herbal medicines are usually preferred for the treatment of skin ailments in comparison to conventional form of medicines due to their safety, low cost and compatibility. But the poor absorption of herbal drugs limits their use in the treatment of various skin ailments. To challenge this problem, active principles of plants have been encapsulated into several nanocarriers like nanoparticles, liposomes or other phospholipid formulations. Materials and Methods: In the present study, vesicles of purpurin-phosphatidyl choline (Pr-PC) complex were prepared and evaluated for the anti-aging activity. For this, initially the complex of Pr with PC was prepared and characterized by thin layer chromatography, differential scanning calorimetry and fourier transform infrared spectroscopy. The complex was converted into vesicles by film cast method. The prepared vesicles were characterized and subjected for in vivo studies to evaluate anti-aging activity. Anti-aging activity of Pr-PC vesicles were compared with plain Pr and Pr-PC complex in ultraviolet-induced oxidative stressed mice model. Results and Discussion: The results of in vivo studies showed the enhanced anti-aging effects of Pr-PC vesicles than other formulations. The increased effectiveness of Pr-PC complex and Pr-PC vesicles may be due to their amphiphilic nature, which enhances the water and lipid miscibility of the Pr. The Pr-PC vesicles were found to be better than Pr-PC complex. This is because of the reduced size of the Pr-PC complex when converted into vesicles. Conclusion: Based on the present study, it can be concluded that the Pr-PC vesicles are superior over Pr–PC complex and plain Pr, in terms of providing enhanced anti-aging properties. Thus, Pr-PC vesicles shown a tremendous potential in enhancing topical delivery of Pr.